AKSIOLOGI BUDAYA BUGIS MAKASSAR TERHADAP PRODUK PERATURAN DAERAH (PERDA) DI SULAWESI SELATAN (Studi Politik Hukum) - Said, Zainal (Jurusan Syariah dan Ekonomi Islam STAIN Parepare, 2011)
In general most of the tribes in South Sulawesi has a relationship, both in terms of language, as well as culturally. Bugis Makassar in public life, customs is a factor that was crucial. Indigenous is a manifestation of the